ECOLOGY, DISTRIBUTION, AND CONSERVATION CHALLENGES OF THE JAVAN SURILI (Presbytis comata) IN JAVA, INDONESIA - Bahana Aditya Adnan; Suwarno Hadisusanto (Berita Biologi, 2026)
The Javan surili (Presbytis comata), a keystone species in the tropical rainforest ecosystem of Java Island, is facing serious threats from deforestation, hunting, and habitat fragmentation. As an endemic species with a highly restricted, particularly on the island of Java, research on the Javan surili remains considerably limited. Hence, its geographical location and distribution patterns are still not clearly understood. Our literature review aims to determine the current status of the Javan surili and the factors influencing its population decline, as well as to evaluate the effectiveness of various conservation strategies that have been implemented. These findings highlight the importance of a multidisciplinary approach in Javan surili conservation efforts and provide policy recommendations to improve the success of species conservation, especially in its native habitat. Immediate conservation efforts and attention from the primatologist, relevant authorities, and stakeholders are needed to prevent the localized extinction of Javan surili.